Advanced environmental scanning electron microscopy reveals natural surface nano-morphology of condensed mitotic chromosomes in their native state - Neděla, Vilém; Tihlaříková, Eva; Cápal, Petr; Doležel, Jaroslav (Scientific reports, 2024)
The challenge of in-situ handling and high-resolution low-dose imaging of intact, sensitive and wet samples in their native state at nanometer scale, including live samples is met by Advanced Environmental Scanning Electron Microscopy (A-ESEM). This new generation of ESEM utilises machine learning-based optimization of thermodynamic conditions with respect to sample specifics to employ a low temperature method and an ionization secondary electron detector with an electrostatic separator. A modified electron microscope was used, equipped with temperature, humidity and gas pressure sensors for in-situ and real-time monitoring of the sample. A transparent ultra-thin film of ionic liquid is used to increase thermal and electrical conductivity of the samples and to minimize sample damage by free radicals. To validate the power of the new method, we analyze condensed mitotic metaphase chromosomes to reveal new structural features of their perichromosomal layer, and the organization of chromatin fibers, not observed before by any microscopic technique. The ability to resolve nano-structural details of chromosomes using A-ESEM is validated by measuring gold nanoparticles with achievable resolution in the lower nanometre units.
Keywords: Mitosis; Chromosomes; Gold; Microscopy, Electron, Scanning; Humans; mitóza; kovové nanočástice; zlato; lidé; mikroskopie elektronová rastrovací; Metal Nanoparticles; chromozomy